Characteristics of Extreme Precipitation and Their Effect on Bean Yield in Rwanda - Umutoni, Marie Adolatha; Limbu, Paul Tilwebwa Shelleph (Tanzania Journal of Engineering and Technology, 2023)
This study examines the characteristics of extreme precipitation and its effect on bean yield in Rwanda from 1981 to 2017. Over the study area, two rainy seasons, March to May (MAM) and September to December (SOND), account for approximately 80% of total rainfall. The spatial distribution of rainfall over Rwanda revealed that the first three EOF modes of MAM rainfall vary by 72.72 percent over the study period, while the first three EOF modes of SOND rainfall vary by 57.48 percent. The spatial analysis of extreme precipitation reveals that during wet years, the majority of the country's western regions receive significantly more precipitation than the rest. Throughout the study period, the analysis revealed an increasing trend in all extreme precipitation indices. After 2009, a significant increase in the number of wet days (R1mm) and consecutive dry days (CDD) was observed, as was an increase in the number of consecutive wet days (CWD) after 2005. From 1981 to 1989, bean yield increased; however, after 1990, the trend became stationary and began to decline after 2012. Except for R1mm, CDD, and CWD, which showed a negative correlation, the correlation analysis revealed a positive relationship between extreme precipitation indices and bean yield. Despite the fact that there is a weak negative correlation between bean yield and CDD, CDD can be used as a predictor of bean yield due to the significant Granger causality test at the 95% confidence level. Farmers are advised to use alternative methods to increase soil moisture and water holding capacity during the CDD period to avoid yield loss. Keywords: Extreme precipitation, extreme precipitation indices, EOF, bean yield.